A national study of firearm exposure and safety training among rural youth - Jamie L. Koopman; Benjamin M. Linden; Megan R. Sinik; Kristel M. Wetjen; Pam J. Hoogerwerf; Junlin Liao; Charles A. Jennissen (BMC, 2024)
Abstract Background Data regarding rural youths' experience with firearms, including safety training, is highly limited despite their frequent presence in homes. Our objective was to investigate rural adolescents' use of firearms and whether they had received formal firearm training. Methods A convenience sample of 2021 National FFA (formerly Future Farmers of America) Convention & Expo attendees were given an anonymous survey at the University of Iowa Stead Family Children's Hospital injury prevention booth. The survey explored their use of rifles/shotguns and handguns and whether they had completed a certified firearm safety course. Descriptive and comparative analyses, including multivariable logistic regression analyses, were performed on compiled data. Results 3206 adolescents ages 13-18 years participated with 45% reporting they lived on a farm or ranch. The vast majority of participants (85%) had fired a rifle/shotgun; 43% reported firing them > 100 times. Of those that had fired rifles/shotguns, 41% had done so before 9 years old. Most had also fired a handgun (69%), with 23% having fired handguns > 100 times. Of those that had fired handguns, 44% had done so before 11 years. Average age for first firing rifles/shotguns was 9.5 (SD 3.1) years, and 11.1 (SD 3.0) years for handguns. Males, non-Hispanic Whites, and those living on farms or in the country had significantly greater percentages who had fired a rifle/shotgun or a handgun. Significant differences were also seen by U.S. census region. Over half (64%) reported having gone hunting. Of those that had used a firearm, 67% had completed a firearm safety training course. Overall, 23% were/had been members of a school or club shooting team and of these, 87% had taken a safety course. Conclusions Most FFA member participants had fired both rifles/shotguns and handguns, many at very young ages. Significant differences in firearm use were noted by demographic factors including the home setting (i.e., farms and ranches) and their U.S. census region. Nearly one-third of adolescent firearm users had not received formal safety training. Promoting firearm safety should include advising families on when it is developmentally appropriate to introduce youth to firearms and on the importance of firearm safety training.